2015
DOI: 10.3389/fpsyg.2015.00696
|View full text |Cite
|
Sign up to set email alerts
|

Visual working memory continues to develop through adolescence

Abstract: The capacity of visual working memory (VWM) refers to the amount of visual information that can be maintained in mind at once, readily accessible for ongoing tasks. In healthy young adults, the capacity limit of VWM corresponds to about three simple objects. While some researchers argued that VWM capacity becomes adult-like in early years of life, others claimed that the capacity of VWM continues to develop beyond middle childhood. Here we assessed whether VWM capacity reaches adult levels in adolescence. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 84 publications
(140 reference statements)
4
54
2
4
Order By: Relevance
“…As such, the current study adds new evidence to the notion that WM continues developing from the 1st year of life (e.g., Riggs et al., ; Simmering, ). It is, however, worth noting that recent visual WM studies have suggested that WM capacity continues developing after 6 years old (e.g., Isbell, Fukuda, Neville, & Vogel, ); however, in Experiment 1, we found that the K value (our index of social WM capacity) had reached the level of adults (cf. Gao et al., ; Shen et al., ) at around 6 years of age.…”
Section: Discussioncontrasting
confidence: 70%
“…As such, the current study adds new evidence to the notion that WM continues developing from the 1st year of life (e.g., Riggs et al., ; Simmering, ). It is, however, worth noting that recent visual WM studies have suggested that WM capacity continues developing after 6 years old (e.g., Isbell, Fukuda, Neville, & Vogel, ); however, in Experiment 1, we found that the K value (our index of social WM capacity) had reached the level of adults (cf. Gao et al., ; Shen et al., ) at around 6 years of age.…”
Section: Discussioncontrasting
confidence: 70%
“…It is not clear whether other theories could accommodate our results with some modification, but at the current level of specificity, no other theory would predict the correlation presented here. Most theories have addressed only increases in capacity (e.g., Cowan et al, 2005; Isbell et al, 2015; Kharitonova et al, 2015; Riggs et al, 2006, 2011) or precision (Burnett Heyes et al, 2012) as potential developmental changes, without considering whether or how the two relate developmentally. These theories are, at the least, under-specified to address our prediction, and at most directly inconsistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Results have shown increasing capacity estimates from early childhood through adolescence (Buss, Fox, Boas, & Spencer, 2013; Cowan et al, 2005; Isbell, Fukuda, Neville, & Vogel, 2015; Kharitonova, Winter, & Sheridan, 2015; Riggs, McTaggart, Simpson, & Freeman, 2006; Riggs, Simpson, & Potts, 2011; Simmering, 2012; Simmering et al, 2015; see Simmering, in press, for discussion of paradigms used to estimate capacity during infancy), although the magnitudes and trajectories of these estimates varies widely across paradigms (see Simmering & Perone, 2013, for related discussion). Most developmental studies have either implicitly or explicitly endorsed a slot-like view, suggesting that the number of items that can be represented increases without addressing whether there are corresponding changes in resolution (e.g., Cowan et al, 2005; Isbell et al, 2015; Kharitonova et al, 2015; Riggs et al, 2006, 2011). …”
Section: Developmental Changes In Visual Working Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Working memory emerges in infancy and develops rapidly over the first year of life (16)(17)(18)(19). It continues to improve during childhood, plateaus in mid-to-late adolescence (20)(21)(22)(23)(24), and declines after age 40-50, albeit less steeply than it changed in early development (25)(26)(27)(28). Developmental gains in working memory follow improvements in attention shifting, attentional maintenance, and distractor suppression (18), whereas changes during later childhood accompany increases in domain-general processing speed and memory capacity (29)(30)(31) with developmental asymptotic performance by adolescence (32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%